(untitled) (Scientia Agropecuaria, 2025)
This study analyzes the potential of 12 seeds from the Peruvian region as by-products of fruit processing, presenting them as a sustainable alternative for waste reduction and the valorization of bioactive compounds. It highlights their chemical composition and the role they can play in recovering bioactive compounds with antioxidant, antimicrobial, and functional properties. The study explores the possibility of utilizing fruit by-products in various industrial sectors, such as food, pharmaceutical, and nutraceutical industries, thereby contributing to the circular economy and a more sustainable management of natural resources. The review emphasizes the importance of addressing challenges such as the presence of antinutrients and contaminants, as well as evaluating processing methods that can reduce these compounds, highlighting the need to ensure their safety for consumption and their viability in different sectors, including food, cosmetic, and pharmaceutical industries.